Development and Optimization of Kunzea ericoides Nanoemulgel Using a Quality by Design Approach for Transdermal Anti-Inflammatory Therapy - Koushik Yetukuri; Marakanam Srinivasan Umashankar (Gels)
This study investigates the Quality by Design (QbD)-driven development and optimization of a nanoemulgel incorporating Kunzea ericoides oil for transdermal therapy. Nanoemulgels enhance percutaneous drug delivery, sustain release profiles, and improve bioavailability. A central composite design was employed to optimize critical formulation parameters, with ANOVA confirming a statistically significant impact on particle size and drug release kinetics (p < 0.05). The optimized formulation exhibited a particle size of 112.38 nm, a polydispersity index of 0.203, and a zeta potential of −29.0 mV, ensuring colloidal stability. In vitro drug release followed the Higuchi model (R2 = 0.989, kH = 4.776), indicating diffusion-controlled kinetics, while the Korsmeyer–Peppas model (n = 0.88) suggested an anomalous transport mechanism. Antibacterial studies determined minimum inhibitory concentrations of 250 µg/mL for Staphylococcus aureus and 500 µg/mL for Escherichia coli, indicating greater susceptibility in S. aureus. In vivo anti-inflammatory evaluation using a carrageenan-induced paw edema model demonstrated a statistically significant reduction in inflammation (p = 0.005 at 60 min), with a near-complete resolution by 240 min. These findings underscore the potential of Kunzea ericoides nanoemulgel as a promising transdermal therapeutic, integrating controlled drug release with potent anti-inflammatory and antibacterial properties for dermatological and inflammatory conditions.